Exploring the Effects of Professional Learning Experiences on In-Service Teachers’ Growth: A Systematic Review of Literature - Zhadyra Makhmetova; Laura Karabassova; Assel Zhakim; Abylay Karinov (Education Sciences)
This systematic review examines the effects of professional learning (PL) experiences on in-service teachers’ self-perceived growth. The study compares formal and informal PL models, drawing on diverse approaches, such as coaching, mentorship, collaborative learning, and reflective practices, to understand how these frameworks impact teachers’ professional efficacy and instructional practices. Using databases like Scopus, Web of Science, and ERIC we analyzed 38 empirical studies, focusing on the teachers’ PL experiences and the resulting self-perceived professional growth across its various domains. The findings indicate that while formal PD sessions (e.g., structured workshops and seminars) support skill development, they often yield mixed results due to their limited adaptability to specific contextual needs. In contrast, informal PL approaches, like mentorship and peer collaboration, foster reflective and practical growth. Combining both PL methods provides the most comprehensive benefits, blending structured learning with the flexibility of informal settings. This review underscores the need for hybrid PL models that address collective and individualized growth pathways, recommending future research into context-sensitive, mixed PL designs to effectively support in-service teachers.